Universal Method of Compatibility Assessment for Novel Ablation Technologies With Different 3D Navigation Systems - Pannone, Luigi; Eltsov, Ivan; Ramak, Robbert; Cabrita, David; Verherstraeten, Marc; Gauthey, Anaïs; Sorgente, Antonio; Monaco, Cinzia; Overeinder, Ingrid; Bala, Gezim; Almorad, Alexandre; Ströker, Erwin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: New technologies for ablation procedures are often produced by different companies with no cross compatibility out of the box. This is a not negligible clinical problem, since those separately developed devices are often used together. The aim of this study was to develop a bench testing method to assess compatibility between the DiamondTemp ablation system (DTA) and Rhythmia electroanatomic mapping system (EAM). Methods: Different setups were tested. DTA was connected to the Rhythmia EAM using the following configurations: 3.1. An Ensite EPT GenConnect box (GCB) and Rhythmia Maestro GCB (Maestro GCB, native Rhythmia setup); 3.2. The Medtronic GCB-E and Maestro GCB; 3.3. The Medtronic GCB-E out via the Medtronic GCB-E directly to the Rhythmia at box 1 (pin A61 to A64). Results: The DTA location was represented in real-time on the Rhythmia EAM. A proper tracking of the DTA was observed in all setups tested by visual comparison of physical catheter movements and its representation on EAM. In the configuration 3.1 a significant shift was observed after the 1st Radiofrequency (RF) application; however further applications did not cause further shift. In setup 3.2 no significant shift has been observed. The setup 3.3 showed a massive shift in catheter position before ablation compared to baseline points acquired using the Orion catheter as a reference. Conclusions: A universal and reproducible solution for compatibility testing between various mapping systems and ablation catheters has been described. DTA has been demonstrated as compatible with Rhythmia EAM with satisfactory results if specific setup is used.